THE EFFECT OF COFFEE SKIN WASTE FERMENTATION (ASPERGILLUS NIGER) WITH DIFFERENT LEVEL IN DIET TO THE GROWTH OF KAMPUNG CHICKEN - N. M. INTAN W. Y. K.; I M. MASTIKA; I M. NURIYASA (Majalah Ilmiah Peternakan, 2018)
An experiment was carried out to study the effect of fermented and not fermented coffee skin waste to the growthof kampong chicken. A completely randomized design, with five treatments and five replications were used so thereare 25 experiment units and each unit consisted of 4 cockerels. The Treatments as of P0: diet without coffee skinwaste (diet control), P1: diet containing non fermented coffee skin waste 10%, P2: diet containing non fermentedcoffee skin waste 20%, P3: diet containing fermented coffee skin waste 10% and P4: diet containing fermentedcoffee skin waste 20%. The variables measured were performance including the final body weight, weight gain,feed consumption, feed conversion ratio, water consumption, and carcass characteristics. Based on result,it can beconcluded that kampong chicken given diet with additional fermented and non fermented coffee skin waste up to20% level has no effect on the growth of kampong chicken age 3-11 weeks, but there is a tendency that the best dietis10% fermented coffee skin.